2018
DOI: 10.24925/turjaf.v6i6.699-709.1720
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Energy Consumption, Carbon Dioxide Emissions and Economic Growth Nexus in Ethiopia: Evidence from Cointegration and Causality Analysis

Abstract: Policy makers need to know the relationship among energy use, economic growth and environmental quality in order to formulate rigorous policy for economic growth and environmental sustainability. This study analyzes the nexus among energy consumption, affluence, financial development, trade openness, urbanization, population and CO2 emissions in Ethiopia using data from 1970–2014. The ARDL cointegration results show that cointegration exists among the variables. Energy consumption, population, trade openness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
5
18
0
Order By: Relevance
“…In the case of the East African region (see Table 1 for a summary of literature), the main focus of our study, few country-specific studies have been conducted using the four most common hypotheses (bidirectional, two unidirectional (growth and conservative), and neutral); nevertheless, these hypotheses were used in several studies, including [9,27,28] and others. Albiman et al [26] revealed the one-way directional causal relationship running from economic growth and energy consumption to CO 2 emissions in Tanzania.…”
Section: Literature View 21 Review Of Research On Co 2 Emissions Rmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the East African region (see Table 1 for a summary of literature), the main focus of our study, few country-specific studies have been conducted using the four most common hypotheses (bidirectional, two unidirectional (growth and conservative), and neutral); nevertheless, these hypotheses were used in several studies, including [9,27,28] and others. Albiman et al [26] revealed the one-way directional causal relationship running from economic growth and energy consumption to CO 2 emissions in Tanzania.…”
Section: Literature View 21 Review Of Research On Co 2 Emissions Rmentioning
confidence: 99%
“…Albiman et al [26] revealed the one-way directional causal relationship running from economic growth and energy consumption to CO 2 emissions in Tanzania. Kebede and Hundie [27,28] used ARDL and Granger causality tests, and results showed a reciprocal relationship between energy and CO 2 emissions, and the causation from economic growth to CO 2 emissions in Ethiopia. Asumadu-Sarkodie et al [29] argued that in Rwanda, an increase in economic growth leads to a decrease in CO 2 emissions, while population growth promotes CO 2 emissions and negatively affects economic growth.…”
Section: Literature View 21 Review Of Research On Co 2 Emissions Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the merits that the ARDL bounds testing approach to cointegration has over the traditional approaches to cointegration (Chindo et al 2014;Halicioglu and Ketenci 2016; (5) Hundie 2018;Shahbaz et al 2015;Shahbaz et al 2013); this study applied the ARDL approach to test the long-run cointegration among the variables under consideration.…”
Section: Cointegration: Ardl Approachmentioning
confidence: 99%
“…They found that a 1 percent increase in GDP per capita leads to a decrease of CO2 emissions by 1.45 percent, but a 1 percent increase in industrialization will increase CO2 emissions by 1.64 percent in the long-run. Likewise, Hundie (2018) assessed the relationship between energy consumption, CO2 emissions and economic growth in Ethiopia between 1970 and 2014. Results showed that energy consumption, population, trade openness and economic growth have a positive effect on CO2 in the long-run, while economic growth squared has a negative relationship with CO2 emissions.…”
Section: Empirical Reviewmentioning
confidence: 99%